Narratives of people who inject drugs on factors contributing to opioid overdose. - Chang, Jamie Suki; Behar, Emily; Coffin, Phillip O. (International Journal of Drug Policy, 2019)
Background: In recent years, there has been increasing national and global attention to opioid overdoses. In San Francisco, it is estimated that the population of people who inject drugs (PWID) has more than doubled in the past ten years. The risk factors for opioid overdose have been examined closely, but firsthand accounts of PWID who have experienced overdoses are less documented. In this paper, we use two theories - lay expertise and structural vulnerabilities - as frameworks to frame and qualitatively examine the narratives of PWID surrounding their recent overdose experiences.Methods: Audio-recorded semi-structured open-ended motivational interviewing counseling sessions were conducted with PWID in San Francisco who have experienced at least one non-fatal overdose event (N = 40). Participants discussed the context of recent opioid overdoses, either witnessed or personally experienced, focusing on their perceptions of unique contributing factors. Interview data were coded and analysed using ATLAS.ti. We used a thematic content analysis approach to qualitatively analyze data queries and generate themes. We used theories of structural vulnerability and lay expertise to frame the analysis.Results: Using quotes from the participants, we report four central themes that contributed to participants' overdose experiences: 1) Social Dynamics and Opioid Expertise; 2) Uncertain Supply, Composition, Source; 3) Balancing Polysubstance Use, and 4) Emotional Pain.Conclusion: As PWID described their overdose experiences, many factors that contributed to their overdoses were situated at the structural level. The everyday, lived experiences of PWID often competed or conflicted with public health messages and approaches. The accumulated expertise of PWID about everyday risk factors can be leveraged by public health practitioners to inform and improve overdose prevention interventions and messages.